Temozolomide-Induced Shrinkage of a Pituitary Carcinoma Causing Cushing's Disease — Report of a Case and Literature Review. (2010) - Curtò, Lorenzo; Torre, Maria L.; Ferraù, Francesco; Pitini, Vincenzo; Altavilla, Giuseppe; Granata, Francesca; Longo, Marcello; Hofland, Leo J.; Trimarchi, Francesco; Cannavò, Salvatore
Abstract : Temozolomide (TMZ) is an alkylating chemotherapeutic agent that has recently been used in some cases as a new therapeutic tool for pituitary carcinomas and aggressive pituitary adenomas. In this report, we present the case of effective TMZ treatment in a 42-year-old man with ACTH-secreting carcinoma. The tumor grew progressively over 4 years, from 2.2 to 31.1 cm 3, despite three surgical approaches and gamma-knife treatment. Ki-67 increased from 2 to 18%. An intradural metastasis at the foramen magnum was detected by MRI after the third operation. Thereafter, four cycles of 5-day TMZ administration (200 mg/m 2 /day during the first, and 150 mg/m 2 /day during the following cycles) induced dramatic tumor size reduction (>90%). Clinical conditions improved progressively and, after 17 months from the beginning of TMZ administration, the patient is still alive. The treatment was well tolerated except for a transient thrombocytopenia (grade 4 WHO).